English fundamentals : form A - Emery, Donald W. [ (Donald William)] , 1906-1993; Kierzek, John M. , 1891-; Lindblom, Peter D. , 1938- (Pearson/Longman, 2007)
"For more than eight decades English Fundamentals hasoffered lucid and strong explanations to reach to students.nbsp; Beginning with the fundamental elements of the sentence, the authorsintroduce the basic system of the language and in progressive lessons explore more complex structures and relationships. nbsp; Solid explanations and a progressive structure move students from the basic level of the sentence to the more complex. nbsp; Solid, clear explanations; an abundance of exercises; numerous diagnostic and progress tests. nbsp; Developmental Writing: Grammar."--BOOK JACKET